Wear evaluation of WC inserts coated with TiN/TiAlN multinanolayers (2010)
TiN/TiAlN multilayers were deposited by radio frequency, r.f., reactive magnetron sputtering by using titanium and aluminum targets with 10 cm diameter and 99.99% purity in an argon/nitrogen atmosphere, applying a substrate temperature of 300 ºC. WC inserts were used as substrates to improve the mechanical and tribological properties of TiN/TiAlN multilayered coatings compared to other types of coatings like TiAlN monolayers and to manage greater efficiency of these coatings in different industrial applications, such as machining, and extrusion. Their physical, mechanical, and tribological characteristics were investigated, including cutting tests with AISI 4340 hardened steel (50 HRC) to assess wear as a function of the period and number of bilayers. A comparison of the properties of TiCN-Al2O3-TiN monolayers coatings and the [TiN/TiAlN]300 multilayers with individual layer thicknesses of 10 nm revealed a decrease of flank wear (around 33%) for [TiN/TiAlN]300 multilayers and a reduction of flank wear (around 13%) for coatings with 300 layers when is compared with [TiN/TiAlN]200 coatings. They also showed better machining properties onto hardened AISI 4340 steel pieces, when compared to uncoated WC inserts. These results open the possibility of using [TiN/TiAlN] multilayers as new coatings for tool machining with excellent industrial performance.